2002
DOI: 10.1038/sj.bjp.0704951
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of hepatic cytochrome P450 in chronic renal failure: role of uremic mediators

Abstract: 1 Chronic renal failure (CRF) is associated with a decrease in liver cytochrome P450 (P450). The mechanism remains poorly understood. The present study aimed to investigate the e ects of the serum of rats with CRF on liver P450. 2 Normal rat hepatocytes were incubated for 24 h with serum (concentration of 10%) from rats with CRF and from control animals in order to measure (1) total P450 level, (2) protein expression and mRNA levels of major P450 isoforms, and (3) some of their speci®c metabolic activities (Nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 33 publications
2
82
0
2
Order By: Relevance
“…As discussed by Sica and Gehr (198), the limited pharmacokinetic studies have not indicated that dosage adjustments of other statins are necessary in renal failure, but the manufacturers have generally recommended lower starting dosages and cautious titration in patients with renal failure. Such recommendations seem prudent given evidence that the state of renal insufficiency has been associated with downregulation of the CYP enzyme system and hepatic metabolism of the drug (201)(202)(203), given the potential alterations in protein binding of these highly proteinbound drugs as a result of uremic toxins, and given the high rate of polypharmacy in this population. As discussed previously, the UK-HARP studies did not indicate higher rates of rhabdomyolysis in patients who had CKD and were treated with simvastatin or ezetimibe/simvastatin (190,192).…”
Section: Safety Of Lld In the Ckd Populationmentioning
confidence: 99%
“…As discussed by Sica and Gehr (198), the limited pharmacokinetic studies have not indicated that dosage adjustments of other statins are necessary in renal failure, but the manufacturers have generally recommended lower starting dosages and cautious titration in patients with renal failure. Such recommendations seem prudent given evidence that the state of renal insufficiency has been associated with downregulation of the CYP enzyme system and hepatic metabolism of the drug (201)(202)(203), given the potential alterations in protein binding of these highly proteinbound drugs as a result of uremic toxins, and given the high rate of polypharmacy in this population. As discussed previously, the UK-HARP studies did not indicate higher rates of rhabdomyolysis in patients who had CKD and were treated with simvastatin or ezetimibe/simvastatin (190,192).…”
Section: Safety Of Lld In the Ckd Populationmentioning
confidence: 99%
“…The main hypothesis to explain P450 activity and expression downregulation is the presence in the blood of uremic animals of endogenous inhibitors that modulate the P450. Indeed, we have shown that in normal hepatocytes that were incubated for 24 h with serum from rats with CRF, total P450 level and protein expression of several P450 isoforms decreased by 45% compared with serum from control animals (11). This decrease in protein expression of P450 isoforms was secondary to reduced gene expression (11).…”
mentioning
confidence: 93%
“…Studies from the Pichette laboratory demonstrated that the activity and expression of cytochrome P-450 (CYP450) was reduced in the 5/6th nephrectomy (5/6N) rat model of chronic renal failure (6,10,11). Their work elucidated a direct role for uremic solutes with the observation that CYP450 activity and expression were reduced in primary rat hepatocytes incubated with human uremic serum (14).…”
mentioning
confidence: 99%